Systemic therapy for brain metastases - Rick, Jonathan W; Shahin, Maryam; Chandra, Ankush; Dalle Ore, Cecilia; Yue, John K.; Nguyen, Alan; Yagnik, Garima; Sagar, Soumya; Arfaie, Saman; Aghi, Manish K. (Critical reviews in oncology/hematology, 2019)
Metastases from cells outside of the central nervous system are the most common cancer found in the brain and are commonly associated with poor prognosis. Although cancer treatment is improving overall, central nervous system metastases are becoming more prevalent and require finesse to properly treat. Physicians must consider the biology of the primary tumor and the complex neurological environment that the metastasis resides in. This can be further complicated by the fact that the practice of cancer management is constantly evolving and therapy that works outside of the blood-brain barrier may not be effective inside of it. Therefore, this review seeks to update the reader on recent advancements made on the three most common sources of brain metastases: lung cancer, breast cancer, and melanoma. Each of these malignancies has been the subject of intriguing and novel avenues of therapy which are reviewed here.